Effects of the alien species Rhithropanopeus harrisii on nutrient levels and benthic fauna communities on the soft bottoms of the Archipelago Sea - Mikkola, Salla (fi=Turun yliopisto|en=University of Turku|, 2016)
Alien species are considered one of the biggest threats to biodiversity. Alien species interact with local species by predation and competition, but they can also change the environmental factors in their introduced area. These chances in the environment also affect local species, usually changing the community structure. Species that alter their environment are called ecosystem engineers. One way in which ecosystem engineers can affect their environment in marine habitats is bioturbation, movement of particles in the sediment. Bioturbation can, for example, affect the cycles of nitrogen and phosphorus between the water column and sediment. The North American mud crab Rhithropanopeus harrisii (Gould 1841), the alien species studied in this thesis, causes bioturbation in the Baltic Sea by hiding from predators and searching for food in the sediment. As an omnivore R. harrisii is a potential predator to benthic fauna, which themselves can oxidize sediment, increasing the area for nitrification. It is possible that R. harrisii lowers the diversity of the benthic fauna via predation, consequently decreasing their effort to oxidize the bottom sediment. In this thesis, I studied the effects of R. harrisii on the benthic faunal communities and nutrient levels of the soft sediment bottoms of the Finnish Archipelago Sea. To test these effects, we conducted a field experiment with two treatments and a control: low abundance treatment with one R. harrisii individual, high abundance treatment with three individuals, and control with no R. harrisii. We placed cages in the soft sediment and placed the individuals in the treatment cages. After three weeks, we took nutrient and benthic samples from the sediment inside the cages. Concentrations of phosphate, ammonium nitrogen, and nitrate nitrogen were analyzed, and I calculated and identified benthic fauna species to species, genus or family level, and calculated Shannon diversity indices for the benthic faunal communities. The presence of R. harrisii did not have a statistically significant effect on the nutrient levels of the sediment, the number of species, or the diversities or structure of the benthic faunal communities. However, there was a slight trend of low abundance of R. harrisii increasing the number of species and diversities and decreasing the levels of nitrogen and phosphorus in the sediment. Thus, in this study, R. harrisii does not seem to affect the benthic faunal communities or nutrient cycling on the soft bottoms of the Archipelago Sea.